Rat brain polyamines: an analytical method validation Poliaminas no cérebro do rato: validação de método analítico - Valdomiro de Freitas Sampaio; Gilberto J. Padovan; Julio Sérgio Marchini; Luiz Marcellino de Oliveira; Sebastião Sousa Almeida (Sociedade Brasileira de Patologia Clínica, 2010)
The validation of the analytical technique for the determination of polyamines in cerebral tissue using HPLC based on o-phthalaldehyde post-column derivatization is described. The polyamines were separated in a LiChrospher100 RP18 column. Elution gradient was formed with two mobile phases: A (sodium acetate 0.1 M + sodium octanesulphonate 0.01 M, pH = 4.5) and B (sodium acetate 0.2 M + sodium octanesulphonate 0.01 M)/acetonitrile (10:3), pH = 4.5) in a 1.2 ml/min flow rate. The derivative eluent was monitored by fluorescence (excitation, 345 nm; emission, 455 nm). Besides excellent linearity (putrescine, r = 0.9816; spermidine, r = 0.9920; spermine, r = 0.9901), the technique demonstrated intra and inter-day precision (< 20%) as well as recovery (spermidine = 92.56%; spermine = 84.47%). Quantification limits were 0.22 pM for putrescine, 76.44 pM for spermidine and 51.44 pM for spermine. The method demonstrated to be robust, simple and highly reproducible for polyamine determination in tissues. A validação técnica analítica para determinação de poliaminas em tecido cerebral utilizando cromotografia líquida de alta eficiência (HPLC) e derivação pós-coluna com o-ftaldialdeído é descrita. A separação das poliaminas deu-se em coluna LiChrospher 100 RP18. O gradiente de eluição foi formado por duas fases móveis A (acetato de sódio 0,1M + octanossulfonato de sódio 0,01 M) e B (acetato de sódio 0,2 M + octanossulfonato de sódio 0,01 M)/acetonitrila (10:3), fluxo de 1,2 ml/min. O eluente foi monitorado por fluorescência (excitação, 345 nm; emissão, 455 nm). Além da excelente linearidade (putrescina, r = 0,9816; espermidina, r = 0,9920; espermina, r = 0,9901), a técnica demonstrou adequada precisão intra e interdia (< 20%) e recuperação (espermidina = 92,56%; espermina = 84,47%). Os limites de quantificação foram 0,22 pM para putrescina, 76,44 pM para espermidina e 51,44 pM para espermina. O método demonstrou ser consistente, simples e altamente reprodutível para a determinação proposta.